Middle and Late Pleistocene terrestrial snails from the Middle Dniester area, Ukraine (based on Mykola Kunytsia’s collections) - Popiuk, Yana; Ridush, Bogdan; Solovey, Tatiana (Polish Geological Institute-National Research Institute, 2021)
Extensive collections of land molluscs from the many sections of Middle and Late Pleistocene deposits, in the region of the Middle Dniester River, were made by Professor Mykola Kunytsia (1925–2002). These collections, now at the Natural Museum, Yuriy Fedkovych Chernivtsi National University, were for the most part analysed but remained partially unpub lished. M. Kunytsia used them for regional reconstructions of palaeolandscapes during various stages of the Pleis to cene. In our study, we used these collections to assess the land snail diversity in the region during consecutive stages of the Middle and Late Pleistocene. Our analysis of faunas of cold and warm stages showed that the latter were more diverse. While all or most of the cold stages had many species in common, the faunas of the warm stages were more heterogeneous. Such a feature may play an essential role in Quaternary biostratigraphy.
Keywords: Middle Dniester; terrestrial molluscs; biodiversity; Pleistocene